PENGARUH PEMASARAN RELASIONAL TERHADAP KEPUASAN NASABAH YANG BERDAMPAK PADA LOYALITAS NASABAH (Studi Pada Nasabah Asuransi Jiwa Bersama (AJB) Bumiputera 1912 Cabang Pematangsiantar) - Klara Delima Agustina; T Teviana (Jurnal PLANS : Penelitian Ilmu Manajemen dan Bisnis, 2017)
Indonesian public awareness the importance insurance Indonesia has been growing rapidly. This condition is seen by the increasing number of insurance companies with a variety of products offered in the community. But even so, awareness of the importance of insurance is not in line with the purchase of an insurance policy. Such conditions make Joint Life Insurance (AJB) Bumiputera 1912 which is a local insurance company to apply the concept of relationship marketing. This study aims to determine the direct and indirect effects of relational marketing consisting of commitment and trust on customer loyalty as well as determine the effect of customer satisfaction on customer loyalty. The population in this study are all policyholders active Joint Life Insurance (AJB) Bumiputera Branch of Pematangsiantar who are customers of at least five years and never filed a claim against the insurance held that as many as 2,750 customers and the sample of 100 people who obtained using the formula slovin with data retrieval random sampling technique. Data was collected by questionnaire at all respondents where the questionnaire was tested beforehand using validity and reliability test on 30 respondents. Technical analysis of the data used is the classical assumption of data normality test, multicollinearity test and linearity test. It is also used path analysis model (path analysis) to examine the direct and indirect influences between variables with hypothesis testing using t test with significance level of 5% (0.05). The results showed that the partial commitments positive influence directly or indirectly on customer loyalty, trust negative influence directly and positively impact directly on customer loyalty and customer satisfaction directly positive effect on customer loyalty.                                    Keywords: Relational Marketing, Commitment, Trust, Satisfaction, Loyalty